Characterizing genetic diversity within and between native Nordic horse breeds utilizing and comparing the EquCab3.0 and EquCab_Finn reference genomes - Smogeli, Nathalie; Shutava, Iryna; Ravnafoss, Signa; Kjetså, Maria; Kantanen, Juha; Pokharel, Kisun; Selle, Therese; Mikko, Sofia; Eriksson, Susanne; Berg, Peer (European Cooperative Programme for Plant Genetic Resources, 2026)
Sustainable breeding of native breeds is essential to preserve genetic diversity and cultural heritage. Several native Nordic horse breeds are at risk of extinction and lack genetic characterization. This study aimed to analyze genetic variation and kinship within and among native Nordic horse breeds using whole genome sequence data, and to compare results from using a Finnhorse genome assembly to that of the EquCab3.0 (Thoroughbred) reference genome. The breeds Dola horse, North Swedish horse and Coldblooded Trotter showed close genetic relationship for fixation index (0.04-0.10), and in principal component analysis. The other breeds showed stronger genetic differentiation, especially the Faroese horse with fixation index above 0.21 to all other breeds. This breed had the highest genomic inbreeding of 33% and a heterozygosity of 12%. The Swedish Ardennes showed the lowest inbreeding at 14% and a heterozygosity of 16%. The North Swedish horses had the highest historical Ne of 96, estimated 13 generations back in time, and the Faroese horse the lowest (23). The mean identity by descent varied from 17% for Swedish Ardennes to 40% for Faroese horses. The choice of reference genomes gave minor to moderate differences, suggesting that a closer related reference improves precision for fine mapping and understanding of genetic landscapes of Nordic breeds. Together, the different analyses showed low genetic diversity in all breeds, and the general pattern of relatedness largely agreed with the known breed history. The results underline the importance of maintaining genetic diversity for the survival of the breeds.
Keywords: horse; genome; sequencing; breeds (animals); population genetics; genetic resources